Neuropathic post-COVID pain symptomatology is not associated with serological biomarkers at hospital admission and hospitalization treatment in COVID-19 survivors - Fernández-de-las-Peñas, César; Guijarro, Carlos; Velasco-Arribas, María; Torres-Macho, Juan; Franco-Moreno, Ana; Truini, Andrea; Pellicer-Valero, Oscar; Arendt-Nielsen, Lars (Frontiers in Medicine, 2023)
Objective Evidence suggests that individuals who had survived to coronavirus disease, 2019 (COVID-19) could develop neuropathic post-COVID pain. This study investigated the association of serological biomarkers and treatments received during hospitalization with development of neuropathic-associated symptoms. Methods One hundred and eighty-three (n = 183) previously hospitalized COVID-19 survivors during the first wave of the pandemic were assessed in a face-to-face interview 9.4 months after hospitalization. Nineteen serological biomarkers, hospitalization data, and treatment during hospitalization were obtained from medical records. Neuropathic pain symptoms (Self-Report Leeds Assessment of Neuropathic Scale), sleep quality (Pittsburgh Sleep Quality Index), pain catastrophizing (Pain Catastrophizing Scale) and anxiety/depressive levels (Hospital Anxiety and Depression Scale) were assessed. Results The prevalence of post-COVID pain was 40.9% (n = 75). Fifteen (20%) patients reported neuropathic symptoms. Overall, no differences in hospitalization data and serological biomarkers were identified according to the presence or not of neuropathic-associated symptoms. Patients with post-COVID pain had the highest neutrophil count, and post hoc analysis revealed that patients with neuropathic post-COVID associated symptoms had lower neutrophil count (p = 0.04) compared with those without neuropathic pain, but differences were small and possible not clinically relevant. No differences in fatigue, dyspnea, brain fog, anxiety or depressive levels, poor sleep, or pain catastrophism between patients with and without neuropathic symptoms were found. Conclusion It seems that neuropathic-like post-COVID pain symptoms are not associated with neither of assessed serological biomarkers at hospital admission nor hospitalization treatments received in this cohort of hospitalized COVID-19 survivors.